Structural and bio-stratigraphic records of Janakor valley in north-western Himalayas, Pakistan: Implications for closure of Neo-Tethys Ocean - Jamal, Ferdous; Qiu, Liang; Faisal, Shah; Khan, Suleman; Ullah, Rafi; Naseer, Ahsan; Zhang, Qihui; Yan, Dan-Ping; Zhou, Zhicheng (Journal of Asian Earth Sciences: X, 2025)
[Display omitted] •Tethyan Ocean closure is marked by marine units below and fluvial deposits above.•Opposite thrusts and varying rock behavior cause complex folds and fault structures.•Folding and thrusting reflect ongoing tectonics controlled by the Main Boundary Thrust. The closure of the Tethys Sea, driven by the collision between the Indian and Eurasian plates, represent a significant event in Earth’s tectonic history. However, many aspects of its structural and stratigraphic implications remain poorly understood. This study investigates on the structural style and biostratigraphic framework of the northwestern Himalayas, focusing on the region at the junction of the Attock-Cherat and Kalachitta Ranges, where deformation is dominated by two major faults, e.g., the Hissartang Fault in the Attock-Cherat Ranges to the north and the Janakor Fault along the Main Boundary Thrust (MBT) to the south. Our analysis reveals a tectonostratigraphic sequence ranging from the Cambrian to the Miocene. Notably, units from the Mid-Cretaceous, Early Paleocene, and Eocene periods are conspicuously absent. Structurally, the region exhibits east–west trending tight, isoclinal folds, where Early and Late Cretaceous units occupy the fold crests and troughs, respectively. Jurassic and Paleocene strata are also involved in deformation, with a network of forethrusts, backthrusts, and overturned thrust contributing to the development of pop-up structure and triangular zones. This study further delineates the boundary marking the Neo-Tethys Ocean closure defined between Eocene marine and Miocene fluvial units. These findings enhance our understanding of the tectonic evolution during this critical period and provide new insights into the kinematic linkage of surface structures with a subsurface décollement within Jurassic strata. This article addresses the scientific challenges of the Neo-Tethys Ocean closure and present a clear and precise account of the structural and biostratigraphic implications of this tectonic event.